TA’DIB SEBAGAI KONSEP PENDIDIKAN: TELAAH ATAS PEMIKIRAN NAQUIB AL-ATTAS - Hasibuan, Albar Adetary (Universitas Nurul Jadid, 2016)
For Al-Attas, the education concept in Islamic world should be ta’dib, not tarbiyah nor ta’lim. Ta’dib has included the meaning of tarbiyah and ta’lim itself. Placing ta’dib as an education concept is representing an ideal one because of the conditions and the problems of education in Indonesia day after day becomes far away from the target. Hence, the foreign cultures take progressively its place as hegemonic in Indonesian education without adaptation process. The main purpose of this research is to explain and comprehend the essense of education of Syed Muhammad Naquib Al-Attas via philosophy of education point of view. Ta’dib as a concept of education has philosophical values which able to be used as reference in the effort of advancing education in Indonesia. In this library reseach,the material object is the philosophy of education of Syed Muhammad Naquib Al-Attas which is included in the masterpieces of Al-Attas. The formal object of this research is the philosophy of education. The method which is used is hermeneutics. This method includes description, interpretation and verstehen. Researcher also use heuristics method in order to find any novelty related to the idea of Syed Muhammad Naquib Al-Attas, especially about education. Hence, there can be found the novelty aspects which able to be used in extending the understanding of education meaning and also new idea to be used in developing philosophy of education study area. The result obtained in this research is the contexteducation worldis experiencingmoraldecadence by the loss of adab. Therefore, ta’dib is the most appropriate solution for education. By running ta’dib as education concept along with the values consisted in it, i.e. the value of justice (‘adl), value of wisdom (hikmah) and adab applied as ‘amal will make education in Indonesia goes more forward. Besides, the target of education is to create a good human being. “Good human being” in the meaning of civilized human being. If ta’dib is applied comprehensively and precisely it will then create an tough civilization.